Dos potenciais evocados miogênicos vestibulares nas orelhas comprometida e assintomática na Doença de Ménière unilateral - Ribeiro, Súnia [UNIFESP] (2005)
AIM: To verify whether vestibular evoked myogenic potentials can present abnormalities in the affected ear and in the asymptomatic ear in patients with diagnosis of unilateral Ménière's disease. STUDY DESIGN: Transversal cohort. MATERIAL AND METHOD: The vestibular evoked myogenic potentials of 20 patients with unilateral Ménière's disease were analyzed. The selection of individuals was based on the history and in clinical evaluation suggestive of unilaterally defined Ménière's disease, and with electrocochleography abnormalities in the affected ear. Vestibular evoked myogenic potentials were evaluated in both ears of each patient through absolute latencies of p13 and n23, interaural difference of latency of peaks p13 and n23 and amplitude p13-n23 asymmetry rate. RESULTS: Vestibular evoked myogenic potentials were altered in 35.0% of the affected ears and in 25.0% of the asymptomatic ears. The alterations were: absence of responses in seven cases, prolongation of p13 latency in three cases, and increase in interaural amplitude difference ratio in one case. CONCLUSION: The vestibular evoked myogenic potentials can present abnormalities in the affected and asymptomatic ears in patients with diagnosis of unilaterally defined Ménière's disease.